Untangling Nickel Downstreaming: A Political Economy Analysis of Indonesia’s Morowali Industrial Park - Jordy, Jordy (International Journal of Social and Political Sciences, 2025)
Indonesia's policy to downstream its nickel industry represents a significant strategic shift aimed at increasing domestic value addition and strengthening its position in the global market. This article analyzes the political economy dynamics of this policy, with a specific focus on the Indonesia Morowali Industrial Park (IMIP) as the central hub of its implementation. This study employs a qualitative case study method, utilizing stakeholder analysis, a Power-Interest Grid, and SWOT analysis to dissect the complex interactions among various actors. The analysis is based on a comprehensive review of academic literature, government regulations, and civil society reports. The findings reveal the formation of a powerful "growth machine" alliance between the Indonesian central government, PT IMIP as the park operator, and foreign investors, primarily from China. While this alliance has successfully driven rapid industrialization and boosted processed nickel exports, it has also generated significant negative externalities. These include the emergence of new forms of dependency on foreign capital and technology, severe socio-environmental degradation, and inequitable distribution of economic benefits, leading to conflicts with local communities and labor groups. The article concludes that while the downstreaming policy has achieved macroeconomic goals, its long-term sustainability is challenged by its failure to foster inclusive and environmentally sound development, presenting a critical paradox for Indonesia's developmental state ambitions.